Analisis Perkembangan dan Potensi Obyek Pariwisata Kota Surakarta - Pamungkas, Mardha Agustin, Dr. Kuswaji Dwi Priyono, M.Si (2017)
Analysis of internal and external potencies indicated that tourism object of Kasunanan Palace had high internal and external potencies. Mangkunegaran Palace had high value of internal potency and low value of external potency. Both Sriwedari Public Park and Radya Pustaka Museum had moderate value of internal and external potencies. Ancient Batik Museum had moderate value of internal potency and low value of external potency. Jurug Zoo had low value of internal potency and moderate value of external potency. Priority of tourism object development of Surakarta city started from Kasunanan Palace and Mangkunegaran Palace in which they had classification of high combination potencies, because the two tourism objects had high values of internal and external potencies. While, tourism objects with moderate values of combination potencies were Radya Pustaka Museum, Sriwedari Public Park, Jurug Zoo and Ancient Batik Museum. The tourism objects had low value of combination potencies because they had moderate value of internal potency and low value of external potency or vice versa so that it affected final results. Tourism object with highest scale for development was Kasunanan Palace, because it had combination of cultural and shopping tourism. Next priorities of tourism object development were Mangkunegaran Palace, Ancient Batik Museum, Jurug Zoo, Radya Pustaka Museum and Sriwedari Public Park.